A new species of leafhopper genus Sophonia (Evacanthinae: Cicadellidae: Hemiptera) from India - Jat, Monica; Meshram, Naresh M.; Dey, Debjani (Zootaxa, 2023)
A new evacanthine leafhopper of the tribe Nirvanini, Sophonia submodesta sp. n. (Himachal Pradesh: Nauni), is described and illustrated from India. An annotated key is provided for the identification of all 17 species known under the genus Sophonia reported from the Indian subcontinent. Type material is deposited in the National Pusa Collection, Division of Entomology, Indian Agricultural Research Institute (ICAR-IARI), New Delhi, India.